An extrusion method of tube with spiral inner fins by utilizing generation of spiral outer fins/grooves. Issue 1 (2018) - Kuboki, Takashi; Ishikawa, Michiaki; Kajikawa, Shohei; Murata, Makoto
Abstract: This paper presents a new extrusion method for fabrication of a tube with spiral inner fins. The spiral fins are formed by utilizing the generation of spiral outer fins or grooves, which drive the metal to circumferentially move with twist deformation. The effect of the outer fins/grooves is examined for realizing the circumferential metal flow. The position of the mandrel has an ability to flexibly control the spiral angle. This method would drastically enhance the productivity and reduce the manufacturing cost, as the tube would be manufactured directly from a billet through only one process.